2016
DOI: 10.3382/ps/pew041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rooster semen enrichment with oleic acid on the quality of semen during chilled storage

Abstract: Liquid storage of avian spermatozoa is currently being employed in programs utilizing the artificial insemination to optimize the management of genetically superior males. It is mandatory to use efficient semen storage techniques in order to prevent the reduction of the fertilizing ability of stored semen. The present study was designated to evaluate the effect of oleic acid on rooster semen quality stored at 4°C for 48 h. Semen was collected from 10 roosters twice a week. Good quality ejaculates were pooled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Irreversible damages and changes in the function and fertilization potential of spermatozoa has been reported during cooling process of semen sample ( Yeste, 2016 ). Enrichment of semen extender have been proposed to ameliorate oxidative toxicity during semen storage as liquid or freeze state ( Câmara et al, 2011 ; Eslami et al, 2016 ; Benhenia et al, 2018 ; Ghaniei et al, 2019 ). Results of the current study revealed the higher amounts of MDA in β-cyfluthrin alone exposed group compared to β-cyfluthrin plus 10 and 25 mM trans -FA treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible damages and changes in the function and fertilization potential of spermatozoa has been reported during cooling process of semen sample ( Yeste, 2016 ). Enrichment of semen extender have been proposed to ameliorate oxidative toxicity during semen storage as liquid or freeze state ( Câmara et al, 2011 ; Eslami et al, 2016 ; Benhenia et al, 2018 ; Ghaniei et al, 2019 ). Results of the current study revealed the higher amounts of MDA in β-cyfluthrin alone exposed group compared to β-cyfluthrin plus 10 and 25 mM trans -FA treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that rooster semen supplementation with quercetin improved sperm parameters such as forward progressive motility, viability and plasma membrane integrity during hydrogen peroxide‐induced oxidative toxicity. Protective effects of substances with antioxidant properties on rooster sperm motility and viability were demonstrated (Eslami et al., ; Lotfi et al., ; Mirzaei Rad, Eslami, & Ghaniei, ). Moreover, the positive association between progressive motility and fertility following insemination was shown in avian (Fattah et al., ; Lotfi et al., ; Moghbeli et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that endogenous antioxidant capacity of semen is not sufficient to conquer oxidative damage during storage (Aurich, Schönherr, Hoppe, & Aurich, ). Semen enrichment with various compounds and antioxidants ameliorate detrimental effects of ROS and lipid peroxidation during chilled storage or after freeze–thawing process in different species, including boar (Funahashi & Sano, ), bull (Munsi, Bhuiyan, Majumder, & Alam, ), ram (Maxwell & Stojanov, ), stallion (Aurich et al., ), rooster (Eslami, Ghaniei, & Mirzaei Rad, ; Lotfi, Mehri, Sharafi, & Masoudi, ; Moghbeli et al., ) and cat (Baran et al., ) semen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, we aimed to improve the quality of semen by improving the antioxidant capacity of aging roosters using dietary ASTA. Moreover, it has been demonstrated that antioxidant capacity plays an important role in maintaining sperm viability because it can protect against lipid peroxidation in semen [39]. MDA is an important indicator of lipid peroxidation.…”
Section: Relationship Between Semen Quality and Antioxidant Enzyme Activitymentioning
confidence: 99%